Africana race and communication : a social study of film, communication, and social media - Conyers, James L., Jr; Conyers, James L., Jr (Lexington Books, 2017)
This volume seeks to identify the interconnection of theory, methodology, and praxis concerning social science studies of African Americans in communication, film, and media.